DOP61 A nationwide cohort study of colectomy rates for ulcerative colitis during the introduction of biologic therapy. (25th January 2019) - Worley, G; Almoudaris, A; Bassett, P; Segal, J; Akbar, A; Aylin, P; Faiz, O
Abstract: Background: Conflicting studies exist regarding changing colectomy rate for ulcerative colitis (UC) over time. Clinical trials suggest high-cost biologic medications reduce colectomy rates, but this has not been corroborated in English population data. This study aimed to use English population-level data to investigate colectomy rates over time during the introduction of infliximab use for UC. Methods: The Hospital Episode Statistics (HES) were interrogated between 2003 and 2016. Emergency cohort inclusion criteria: UC primary diagnosis or secondary diagnosis with a primary acute colitis diagnosis, age >17, emergency admission ≥ 3 days. Total population cohort inclusion criteria: All colectomies with a primary UC diagnosis. Infliximab (IFX) coding was available from 2006. Kaplan–Meier, Cox regression, and average annual percentage change (AAPC) were used to investigate colectomy rate over time. Interrupted time series (ITS) analysis was used to investigate colectomy rate change after National Institute for Clinical Excellence (NICE) approval for IFX use in moderate–severe UC in December 2008. Results: Emergency cohort: 37981 patients included; 49% female and median age 46. Cumulative incidence of colectomy at 30 and 90 days, 1, 3, and 5 years after emergency admission was 0.10, 0.12, 0.17, 0.21, and 0.23, respectively (SE 0.002) Line graph showing annual colectomy rate by admission year for various colectomy intervals and annual Infliximab use Figure 1 shows colectomy rates at 30 days, 1 and 3 years, and rate of IFX use within 30 days by year. AAPCs for 30-day, 90-day, 1-, 3-, and 5-year colectomies were −1.6, −1.3, −1.8, −0.7 and −0.3, respectively. AAPC for 30-day IFX use was +52.6. ITS showed changes in 30 and 90-day colectomy rates but not 1 or 3 years (Table 1) Population cohort: 17580 UC colectomies included. AAPCs for total, emergency and elective cases were −1.31, −0.24, and −1.83, respectively. ITS analysis showed reduction in colectomy rate after 2008 of 2.4% per year. Conclusions: Mixed analyses suggest that the rate of colectomy has decreased modestly over time. In some cases, rates reduce after 2008 but this is likely multi-factorial, as the IBD Standards were also introduced in 2009. The reduction in short-term colectomy rates is not reflected in medium-term colectomy rates. It is not clear whether the reduction in colectomy rates has plateaued or is still reducing. A lack of clinical information regarding disease severity precludes further detailed interpretation.